2015
DOI: 10.5296/ijrd.v2i2.6237
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Choice of Marketing Outlets among Small-Scale Pineapple Farmers in Kericho County, Kenya

Abstract: Markets act as pivotal point in the agricultural transformation process. Access to market plays crucial role in exploiting the marketing opportunities for the pineapple farmers. In the study area, the strategies to unlock the market access among pineapple farmers are wanting and these have resulted to limited marketing outlets. This study therefore seeks to determine the factors influencing the choice of pineapple marketing outlets in Bureti district. The cross-sectional data were collected from a sample of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
29
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 3 publications
8
29
2
3
Order By: Relevance
“…This reveals that when these traders are encouraged to form their own organizations, they will be in position to promote formal trade, since they will have a uniform voice to bargain for fair taxes, and policies that favor them in general. This finding is in agreement with Sigei et al (2015) who indicated that farmers that were in a marketing group were influenced to market in urban markets whereas, those that were not in the group marketed in local market or at farm gate.…”
Section: Determinants Of Traders Choice Of Fish Marketing Channelssupporting
confidence: 82%
“…This reveals that when these traders are encouraged to form their own organizations, they will be in position to promote formal trade, since they will have a uniform voice to bargain for fair taxes, and policies that favor them in general. This finding is in agreement with Sigei et al (2015) who indicated that farmers that were in a marketing group were influenced to market in urban markets whereas, those that were not in the group marketed in local market or at farm gate.…”
Section: Determinants Of Traders Choice Of Fish Marketing Channelssupporting
confidence: 82%
“…In addition, women also spend much of their time doing house work and allocate less time to other matters like market transactions (Wang'ombe, 2008). This finding is similar to the finding of Cunningham et al (2008), Wang'ombe (2008), Sigei et al (2013) and Sebatta et al (2014). However, this finding is different from that of Onoja et al (2012) in which they found a higher probability of fish commercialization if the head of the household is female.…”
Section: Market Participation and Welfare: Heckman Two-step Modelcontrasting
confidence: 53%
“…This position is also supported by other studies, for example [8], where the explanatory variables jointly influenced the extent of market commercialization. Other relevant studies where combinations of variables were identified as influencing market participation decisions, either positively or negatively, among surveyed smallholder farmers include [23,35] and also [67].…”
Section: Effect Of Identified Variables On Market Participationmentioning
confidence: 99%
“…Few studies have focused on how the use of ICT-based market information sources influence the market participation of smallholder livestock farmers, as most have reported mainly on crop farmers [20][21][22]. Also, many of the available studies that have focused on the factors influencing market participation among farmers have not emphasized the contribution of market information sources in determining participation [23][24][25]. Hence, Souter [26] articulated the importance of information sources while outlining the different values that farmers ascribe to various communication methods and channels.…”
Section: Introductionmentioning
confidence: 99%